A Pre-Experimental Study on the Effect of Proning Position on Oxygen Saturation in Pulmonary Tuberculosis Patients - Rahmayanti, Yeni Nur; Nugroho, Yohanes Wahyu (Chakra Brahmanda Lentera Institute, 2025)
Background: Pulmonary tuberculosis (TB) is an infectious disease that primarily affects the lung parenchyma. Common moderate symptoms include dyspnea and hypoxemia. Prompt and effective management of hypoxia is crucial to prevent further organ damage. One non-invasive and easily administered intervention is the use of the proning position, which facilitates improved oxygen intake. This study aims to examine the effect of the proning position on increasing oxygen saturation in patients with pulmonary tuberculosis. Methods: This pre-experimental study used a one-group pretest–posttest design. The study involved 35 patients with pulmonary TB treated in the Wijaya Kusuma 3 Ward of Kartini Karanganyar Regional Public Hospital during December 2023. Inclusion criteria were: drug-sensitive pulmonary TB, oxygen saturation <94%, fully conscious, no severe respiratory distress, and willingness to participate. Exclusion criteria included unstable hemodynamics, spinal injuries, or contraindications to positional changes. Each patient underwent a series of five proning positions (prone, right and left lateral, and right and left semi-sitting side-lying), with each position held for 30 minutes. Oxygen saturation levels were measured before and after the intervention. Data were analyzed using a paired t-test. Results: The mean oxygen saturation increased from 93.87% before the intervention to 96.97% after the proning technique. Post-intervention saturation ranged between 96% and 99%. Statistical analysis showed a significant improvement in oxygen saturation following the intervention (p < 0.001) Conclusion: The proning position significantly improves oxygen saturation in patients with pulmonary tuberculosis. It is recommended as a supportive, non-invasive intervention for managing hypoxemia in pulmonary TB cases.